فعالية وأمان استعمال سكروز الحديد الوريدي في معالجة فقر الدم عند مرضى التحال الدموي المزمن - عباس عبد الفتاح (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في وحدة التحال الدموي في مشفى الأسد الجامعي باللاذقية وشملت 41 مريضاً يخضعون للتحال الدموي المزمن لفترة تزيد عن ستة أشهر ويعالجون بهرمون الإريتروبوئيتين منذ أربعة أشهر على الأقل دون أن يتجاوز مستوى الخضاب عندهم 10غ/دل وكان مستوى الفيريتين عندهم عند بداية الدراسة أقل من 100مكغ/ل (نقص حديد مطلق). أعطي جميع مرضى الدراسة سكروز الحديد بالحقن الوريدي البطيء بجرعة 100ملغ مرة واحدة أسبوعياً ولمدة ثمانية أسابيع. وبنتيجة الدراسة ارتفع متوسط الخضاب عندهم من 7.28 إلى 10.36 (p<0.001) كما ارتفع متوسط الفيريتين من 76.36 إلى 460.53 (p<0.0001) ولم تظهر أية تفاعلات تحسسية عند أي من مرضى الدراسة مما يظهر فعالية هذا العلاج وأمانه عند مرضى التحال الدموي المزمن. This study was carried out in the Hemolialysis Unit at AL-Assad University Hospital, Lattakia, and included 41 patients on chronic hemodialysis for more than 6 months, treated by erythropoietin for 4 months at least with hemoglobin concentration less than 10 gand serum ferritin less than 100 (absolute iron deficiency) at the beginning of the study. All patients received iron sucrose (100 mgper week for 8 weeks) by slow intravenous injection. We found out that mean hemoglobin level increased from 7.28 to 10.36 (p< 0.001) and mean serum ferritin level increased from 76.36 to 460.53 (p< 0.0001) and none of the patients developed hypersensitivity reactions. We conclude that iron sucrose is effective and safe in hemodialysis patients.